Bilateral abducens nerve palsy from post-spinal-anesthesia-induced bilateral chronic subdural hematoma: case report - Shiferaw, Mestet Yibeltal; T/Mariam, Tsegazeab Laeke; Aklilu, Abenezer Tirsit; Shumbash, Kibruyisfaw Zewudie; Akililu, Yemisirach Bizuneh; Worku, Bethelhem Yishak; Ayele, Mengistu (Frontiers in Anesthesiology, 2023)
Chronic cranial subdural hematoma (CSDH) following post spinal anesthesia is among the rare, but serious and life-threatening complication of spinal anesthesia. It usually mimics the common post spinal anesthesia headache or post dural puncture headache (PDPH), potentially masking its detection. Abducens nerve palsy tends to occur in chronic subdural hematoma of post dural puncture etiology than other causes of subdural hematoma. Preferential damage to the abducens nerve is very common and can be explained by its anatomic course as the abducens nerve runs in the direction of the typical caudad displacement of the brain related with intracranial hypotension.We are presenting the clinical presentation, pathogenesis and management of two cases that developed bilateral abducens nerve palsy following post spinal anesthesia administered for cesarean section for an obstetric indication.Post spinal anesthesia induced chronic subdural hematoma though a rare life-threatening complication, it must be differentiated from post spinal anesthesia headache and treated surgically. Cranial nerve palsy (more commonly abducens nerve palsy) is more common in post spinal anesthesia induced subdural hematoma than subdural hematomas of other etiology as the CSF brain cushing is partly lost. The cranial nerve palsies recover in majority of cases if surgery is performed timely.